Analisis Sertifikasi Halal dalam Meningkatkan Penjualan pada Usaha Haysanadi Catering Service - Rofiuddin, Mohammad (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2023)
Halal certification is an important legality of food to guarantee its Islamic halalness. In its implementation, Haysanadi Catering service experienced significant changes in income before and after having halal certification. The purpose of this research is to conduct analysis research on halal certification in increasing sales. This type of research is field research using direct observation and data collection. The approach method used is descriptive qualitative using data collection techniques such as observation, interviews and documentation. The research results show that halal certification at Haysanadi catering service can increase sales. Halal certification is able to increase consumer confidence because they no longer doubt the food they buy, is able to reach new markets because when customers are satisfied they will recommend it to others, shows concern for Islamic law because the majority of the market is Muslim, and is able to improve the company's image because the halal label means Maintaining the quality of ingredients from raw products to ready for consumption.